Female sperm storage mediates post‐copulatory costs and benefits of ejaculate anticipatory plasticity in the guppy. (20th July 2020) - Cardozo, Gabriela; Devigili, Alessandro; Antonelli, Pietro; Pilastro, Andrea
Abstract: Males of many species evolved the capability of adjusting their ejaculate phenotype in response to social cues to match the expected mating conditions. When females store sperm for a prolonged time, the expected fitness return of plastic adjustments of ejaculate phenotype may depend on the interval between mating and fertilization. Although prolonged female sperm storage (FSS) increases the opportunity for sperm competition, as a consequence of the longer temporal overlap of ejaculates from several males, it may also create variable selective forces on ejaculate phenotype, for example by exposing trade‐offs between sperm velocity and sperm survival. We evaluated the relationship between the plasticity of ejaculate quality and FSS in the guppy, Poecilia reticulata, a polyandrous live‐bearing fish in which females store sperm for several months and where stored sperm contribute significantly to a male's lifelong reproductive success. In this species, males respond to the perception of future mating opportunities by increasing the quantity (number) and quality (swimming velocity) of ready‐to‐use sperm (an anticipatory response called 'sperm priming'). Here we investigated (a) the effect of sperm priming on in vitro sperm viability at stripping and its temporal decline (as an estimate of sperm survival), and (b) the in vivo competitive fertilization success in relation to female sperm storage using artificial insemination. As expected, sperm‐primed males produced more numerous and faster sperm, but with a reduced in vitro sperm viability at stripping and after 4 hr, compared with their counterparts. Artificial insemination revealed that the small (nonsignificant) advantage of primed sperm when fertilization immediately follows insemination is reversed when eggs are fertilized by female‐stored sperm, weeks after insemination. By suggesting a plastic trade‐off between sperm velocity and viability, these results demonstrate that prolonged female sperm storage generates divergent selection pressures on ejaculate phenotype. Abstract : Poecilia reticulata sperm bundles as seen under a dissection microscope. Each bundle contains approximately 22, 000 sperm cells.